Quantitative Analysis of the Effectiveness of Investment in Education—in the Background of Chinese Provinces and Regions - Xiuhang Gao (Law and Economy, 2023)
With the rapid development of social productivity and science and technology, the importance of education has become increasingly prominent and the relationship between education and the economy has become increasingly close. This paper uses regression analysis to correlate the level of investment in education with the number of enterprise development projects and the gross domestic product through the R language and a series of quantitative analyses. It is concluded that the level of education shows a positive relationship with the number of enterprise projects and the gross product, and the phenomenon is illustrated by data visualisation with the long-term development of the country as the goal.